PENERIMAAN PAJAK DAERAH: Pelajaran Dari Kota Kendari Provinsi Sulawesi Tenggara - isti isti; Muhammad Natsir; Tadjuddin Tadjuddin (JEP (Jurnal Ekonomi Pembangunan), 2018)
There is still a gap between the target and the realization of movie/cinemax tax receipis, restaurant tax, and motorized racing tax in Kendari City. This study aim to find out and analyze: (1) the gap between the target and the realization of movie/cinema tax, restaurant tax, and motorized racing tax (2) the factors that influence the level of movie/cinema tax, restaurant tax, and motorized tax. The type of data data used is primary data and secondary data. The analytical tool that used is descriptive analysis. The results of the study show that: (1) the gap between the target and realization of movie/cinema tax, restaurant tax, and motorized racing tax in Kendari City in 2013-2017 tended to increase with an average gap Rp225.257.700. (b) the gap between the target and realization of restaurant tax in Kendari City in 2013-2017 fluctuated with an average gap Rp152.026.922. (c) the gap between the target and realization of motorized racing tax in Kendari City in 2013-2017 tended to decline with an average gap Rp2.900.000. (2) the factors that influence the level of realization of movie/cinema tax, restaurant tax, and motorized racing tax are : tax payers awareness, data base and potential tax, while the regional regulations regarding taxation and sanctions for non-paying tax don’t affect the level of realization of movie/cinema tax, restaurant tax, and motorized racing tax. For the Government of Kendari City to always try to manage and increase the potential of local taxes and provide the strict sanctions for non-compliant taxpayers so that there is no longer a gap between the target and realization of regional taxes in Kendari City.